THE POSITIONS OF H+, LI+ AND NA+ IMPURITIES IN BERYL - Andersson L.O. (My University, 2006)
Electron Paramagnetic Resonance (EPR) measurements show that Li+ impurities are located at two different positions in beryl, one in the crystal lattice and the other in the crystal channel. The position of the Li+ impurity in the lattice is generally assumed to be at the site of a missing Be2+ ion. It is shown that this is not the case, but that the Li+ ion is located in a tetrahedron formed by the oxygens of one side of the Be tetrahedron and the nearest oxygen in the channel ring. This Li site has the coordinates (0.423, 0.344, 0.167) and can only be occupied when the neighbouring Be site is empty. There are four such sites around every Be tetrahedron at the distance of 1.46 Å from the Be site. The distance from the Li site to the oxygens of the Li tetrahedron is 1.84 Å. This compares favourably with the much smaller distance of 1.65 Å in the Be tetrahedron. Protons in beryl are trapped at or near these Li sites. Na+ is known to be located at the 2b position at the center of the silicate rings, where it is stabilized by one water molecule located at each of the two surrounding 2a sites. This is also the position of Li+ in the beryl channel. It is found that the presence of Na+ in the ring of six oxygens reduces the radius of this ring. The Na+ impurity has also been supposed to be located at position 2a alone and at 2b stabilized by only one water molecule. It is now proposed that Na+ and H2O are located together in the Al–Be plane when only one water molecule is associated with Na+. The water oxygen is located at or near 2a and Na is closer to the Be site in tetrahedral beryl and closer to the Al site in octahedral beryl. It is proposed that the water protons are also located in the Al–Be plane, which would mean that there exists a third type of water in beryl. The origin of protons and OH− ions in beryl is discussed and it is suggested that the plugs in the beryl channels are CO 3 2− ions. Diffusion of OH− ions and natural radiation may have led to the creation of NO3 and the blue colour of Maxixe beryl.
Keywords: LI IN BERYL; BERYL IMPURITIES; MAXIXE-TYPE BERYL; EPR